ANALISIS PENGENDALIAN PERSEDIAAN BERDASARKAN ABC CLASS-BASED DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN REORDER POINT (ROP) - Kafidin Muzakki; Indah Kumalasari; Achmad Wicaksono (.Universitas PGRI Adi Buana, 2022)
Inventory is an important item or asset owned by the company. Sufficient supplies must be maintained. Therefore, it is important to carry out good inventory control by carrying out effective, efficient and economical inventory planning. This research aims to 1) determine the inventory control in J&L clinic, 2) determine the grouping of beauty product in dividing into class A, B and C using Class-Based ABC method, 3) economical order quantity and time to reorder beauty product using the calculation of Economic Order Quantity (EOQ) and Reorder Point (ROP) methods in J&L clinic. The research method used is qualitative method with a descriptive type of research. Data collection technique through beauty product inventory documents, interviews and observations. Subjects or informants in this research is head of warehouse, warehouse staff, and admin staff in J&L clinic. The results showed that the control of the supply of beauty products carried out at the J&L clinic was quite optimal. Inventory planning that has been done is quite good. By looking at the number of requests and previous orders to meet the needs of the availability of goods in the warehouse. The result of grouping the results of class-based abc analysis based on demand and investment value for class A group has the highest number of requests amounting to 78,59% and 77.90% of the total investment value. Class B group has a total demand of 15.98% and 16.93% of the total investment value. class C group has a total demand of 5.44% and 5.17% of the total investment value. The results of the calculation of the EOQ method show that by using the EOQ method, the optimal number of orders for beauty products is more every time you make an order, but the frequency of ordering is less than the company's policy. The ROP method is determined to determine the time of reordering and added safety stock.